Experimental Study on the Pile-Soil Synergistic Mechanism of Composite Foundation with Rigid Long and Short Piles. (4th May 2021) - Guo, Yuancheng; Lv, Chenyu; Hou, Siqiang; Liu, Yunlong
Abstract : The rigid long-short-pile composite foundation has been increasingly used as an effective and low-cost reinforcement method. The pile-soil interaction in this foundation type is more complicated than that in the equal-length pile composite foundation. In this study, several physical model tests were conducted to investigate the pile-soil synergistic mechanism of the rigid long-short-pile composite foundation. A comparative analysis was conducted of the static load test data of single-pile and long-short pile composite foundations to assess the load-bearing characteristics and stiffness evolution of the composite foundation and pile-soil unit. The result indicated a positive correlation between the pile length and the overall bearing capacity of the single-pile composite foundation. The overall stiffness of the four-pile composite foundation was lower than that of the single-pile composite foundation due to an increase in the areas of the soil stress and the pull-down effect caused by multiple piles. The long pile exerted a greater influence on the overall settlement than the short pile. In addition, the correction coefficients were obtained to determine the pile-soil stiffness of the four-pile composite foundation based on that of the single-pile composite foundation, providing a theoretical reference for the optimal design of composite foundations.